COST-BENEFIT IN MARKETING COMMUNICATIONS: AN ACCOUNTING PERSPECTIVE - Silvia Ekasari; Oggy Akmadani (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
Marketing communication is a vital component of modern business strategy, but its effectiveness needs to be accurately measured from a financial perspective. The research method conducted in this study uses the literature method. The results show that a proper accounting approach in evaluating the cost-benefit of marketing communications can improve the efficiency of resource allocation and accountability of the marketing department. With that, a careful cost-benefit analysis from an accounting perspective is critical to the success of a marketing communications strategy.